Narrare per esistere: la (in)visibilità della maternità nella letteratura italiana contemporanea - Reyes Ferrer, Maria (Romanica Silesiana, 2020)
From the second half of the 20th century, the issue of women’s writing has been of considerable interest in literary studies, highlighting the need to know women as writers and as literary subjects, in order to understand female experience first-hand. This approach to written texts is based on two fundamental aspects of study: women as writers and the representation of women in the text. This has made it possible to examine how women are represented and what topics women writers prefer, for example, motherhood, a literary topos par excellence in Italian literature. Despite this, although motherhood is present in numerous works, the voices of actual mothers are largely absent: mothers and motherhood are in fact narrated from the point of view of daughters. In view of that, there are two main aims of this study: (1) to examine the possible reasons for the absence of the mother’s point of view and (2) to analyze some contemporary Italian literarature narrated by mothers themselves.